Netflix's Representation in the Case of 'Cyanide Coffee' in the film 'Ice Cold: Murder, Coffee, and Jessica Wongso: Critical Discourse Analysis Fairclough - Mutakhirani Mustafa; Nelly Husni Laely; Fransiska Densiana; Emi Anggreani; Eka Pitra (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research aims to describe the representation tendencies of Netflix in the documentary film "Ice Cold: Murder, Coffee, and Jessica Wongso." The study applies a qualitative descriptive research method using the Critical Discourse Analysis approach by Fairclough. The data source for this research is the narrative of the documentary film "Ice Cold: Murder, Coffee, and Jessica Wongso" produced by Netflix. The analysis of description results of agency reveal that the agents mentioned by the narrator are Cyanide 37%, Netflix 31%, authorities 13%, Jessica 13%, and All Indonesian people 6%. Thus, the agents mentioned by the narrator in the film "Ice Cold: Murder, Coffee, and Jessica Wongso." Regarding the analysis of narrator data using the theory of transitivity processes, it shows that the most dominant is Pr. Verbal at 24%, followed by Pr. Mental at 23%, and Pr. Material at 23%. The third position is Pr. Existential at 18%, and the lowest is Pr. Behavioural at 12%. Therefore, in the analysis of the narrator's narrative, it is found that both mental and material processes have equal percentages, each at 32%. This analysis identifies that the narrator comprehensively. The interpretation found that the narrator uses material and verbal processes to convey the efforts and hard work of the production team in conducting interviews with all the sources involved in this case. The narrator also predominantly uses mental processes because the narrator conveys and convinces the public about the facts of cyanide unknown to the public. The narrator convinces the public that the knowledge about cyanide with facts and evidence in Mirna's case cannot be considered the cause of Mirna's death. The explanation Netflix's efforts to bring in several narrators, even with the absence of some key narrators, become a question mark. Jessica, as a suspect in Mirna's death case, is hard to find. Netflix's belief is that Mirna's death is not because of cyanide. Netflix also has an interest in gaining significant profit from making this film, as evidenced by the trailer being watched by as many as 44 million viewers, and the documentary becoming one of the most popular documentaries produced by Netflix.